Navigated laser (navilas) therapy for choroidal neovascular and hyperpermeability pathologies - Alshahrani, Saeed T. (2015)
Purpose: To report the utility of navigated laser (NAVILAS) in the treatment of leaking areas in central serous chorioretinopathy and a feeder vessel in choroidal neovascular membrane. Methods: Two patients with choroidal lesions were treated with NAVILAS. The first patient had central serous chorioretinopathy with visible leaking angiographic spots, and the second had choroidal neovascular membrane with a well-defined feeder vessel on angiography. Both patients underwent NAVILAS treatment. Results: Both patients were successfully treated with resolution of clinical symptoms after a single session of NAVILAS. In addition, complete resolution of the subretinal fluid and leakage, and the subretinal blood and feeder vessel, were noted in the central serous chorioretinopathy and feeder vessel cases, respectively. Conclusion: NAVILAS may be of utility in targeting choroidal vascular pathologies with laser.